Electrode length measurement in electric arc furnaces - Ballard, Norman (Department of Electrical Engineering, 2016)
Accurate measurement of electrode length in electric arc furnaces will result in decreased maintenance time, and improved plant productivity. This thesis describes the development of a microwave-based Soderberg electrode length-measurement system. Various methods of electrode-length measurement were investigated, and it was found that a microwave measurement system based on a conventional frequency modulated continuous wave (FMCW) radar presented the most feasible technique. In this system, microwaves are propagated down a waveguide placed in the electrode. As the waveguide melts, they continue propagating in the resulting cavity until they are reflected by the discontinuity at the bottom of the electrode. The time taken for the return journey to the bottom of the electrode and back is measured, and the electrode length calculated.